PENGEMBANGAN APLIKASI BERBASIS AUGMENTED REALITY SEBAGAI MEDIA INFORMASI DAN PROMOSI PADA LPK “ZARAYA LIHAY”: DEVELOPMENT OF AN ANDROID-BASED AUGMENTED REALITY APPLICATION FOR INSTITUTIONAL INFORMATION AND PROMOTION: A CASE STUDY OF THE ZARAYA LIHAY VOCATIONAL TRAINING CENTER - awang pradana; Annida Zakkiah Az-zahra (LPPM Universitas Abdurrab, 2026)
Augmented Reality (AR) has emerged as an innovative medium for delivering interactive information beyond the limitations of traditional promotional tools such as brochures. This study presents the design, development, and evaluation of an Android-based AR application for vocational training institutions. The system employs a marker-based approach to provide interactive three-dimensional visualizations of institutional information, including instructors, training packages, vehicles, and learning materials. Performance testing under various lighting conditions consistently achieved a 100% detection rate, while marker occlusion tests reported an average success rate of 78.33%. The usability evaluation explicitly involved 20 respondents and produced a final overall score of 4.94 out of 5 (98.92%), indicating excellent learnability, efficiency, and user satisfaction. The findings confirm that the proposed AR application offers a practical, innovative, and user-friendly solution for enhancing institutional information delivery and promotional effectiveness.